2020
DOI: 10.7860/jcdr/2020/44800.13952
|View full text |Cite
|
Sign up to set email alerts
|

Engaging School Going Children During COVID-19 Lockdown

Abstract: Corona Virus Disease 2019 (COVID-19) pandemic is current crisis in more than 200 countries in the world. The virus originated in bats and was transmitted to humans in December 2019 via still unknown intermediate animals in Wuhan, Hubei Province, China. In India, Corona virus confirmed cases are 101,139, recovered cases are 39,174, deaths 3,163 and active cases are 58,802 on the date of 19 May 2020. “In India, Prime Minister Narendra Modi declared phase wise complete lockdown for corona virus pandemics to save … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…A number of studies related to Covid pandemic were reported [28][29][30]. Some of the related studies were reviewed [31][32][33][34].…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies related to Covid pandemic were reported [28][29][30]. Some of the related studies were reviewed [31][32][33][34].…”
Section: Discussionmentioning
confidence: 99%
“…The world had to again revert to the need for non-pharmaceutical interventions, in the initial absence of a vaccine, to limit the spread of COVID-19. Guidance and rapidly undertaken/delivered research studies on these restrictions have occurred, for example, on self-isolation ( Arden et al , 2020 ; Smith et al , 2020 ), working from home ( Hadi et al , 2021 ; Kinman et al , 2020 ; Toniolo-Barrios & Pitt, 2021 ; Vyas & Butakhieo, 2021 ), school closures which affected over 1.5 billion (85%) of school children worldwide, liable to increase educational inequalities ( Grewenig et al , 2020 ; Kasturkar & Gawai, 2020 ; UNESCO, 2021 ); quarantine periods with the psychological impact and perception on quality of life ( Brooks et al , 2020 ; Lardone et al , 2020 ), and social distancing experienced barriers and facilitators for adult ( Coroiu et al , 2020 ) and young people ( Public Health Agency Behaviour Change Group, 2020 ). The restrictions (although needed) and their consequential impact, have had a profound effect on all aspects of society, including physical and mental health, and many of the direct and indirect consequences are still not fully known ( Holmes et al , 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…The world had to again revert to the need for non-pharmaceutical interventions, in the initial absence of a vaccine, to limit the spread of COVID-19. Guidance and rapidly undertaken/delivered research studies on these restrictions have occurred, for example, on self-isolation (Arden et al, 2020;Smith et al, 2020), working from home (Hadi et al, 2021;Kinman et al, 2020;Toniolo-Barrios & Pitt, 2021;Vyas & Butakhieo, 2021), school closures which affected over 1.5 billion (85%) of school children worldwide, liable to increase educational inequalities (Grewenig et al, 2020;Kasturkar & Gawai, 2020;UNESCO, 2021); quarantine periods with the psychological impact and perception on quality of life (Brooks et al, 2020;Lardone et al, 2020), and social distancing experienced barriers and facilitators for adult (Coroiu et al, 2020) and young people (Public Health Agency Behaviour Change Group, 2020). The restrictions (although needed) and their consequential impact, have had a profound effect on all aspects of society, including physical and mental health, and many of the direct and indirect consequences are still not fully known (Holmes et al, 2020).…”
Section: Introductionmentioning
confidence: 99%